Sustainable approach to recover β-carotene and astaxanthin from Phaffia rhodozyma grown in a stirred-tank bioreactor under the influence of magnetic fields - Silva, Pedro Garcia Pereira; Mussagy, Cassamo U.; Lima, Caio de Azevedo [UNESP]; Santos-Ebinuma, Valéria C. [UNESP]; Burkert, Janaína Fernandes de Medeiros; Santos, Lucielen Oliveira (Elsevier, 2023)
This study aimed to produce carotenoids by Phaffia rhodozyma in a stirred-tank bioreactor under the influence of magnetic fields (MF) and to evaluate a sustainable approach to recover them from the yeast biomass. MF application proved to be effective in increasing 8.6 and 22.9 % of β-carotene and astaxanthin production, respectively. Regarding solid–liquid extraction (SLE), the ability of aqueous and ethanolic solutions of protic ionic liquids (PILs) was determined. β-carotene and astaxanthin recovery yields increased with the anion alkyl chain length hydrophobicity. [Pro][Oct]:EtOH (50 % v v-1) was selected as the effective solvent. Moreover, it led to improvement in carotenoid stability at different storage temperatures over time in comparison with the control. This study is one of the first to describe an effective and sustainable approach to move carotenoid production from shake flasks to a bioreactor under the influence of MF and recover carotenoids from P. rhodozyma biomass.
Keywords: Carotenogenic extract; Carotenoid production; Magnetic effect; Phaffia rhodozyma; Protic ionic liquid